Mental workload analysis of Industrial Engineering students using Subjective Workload Assessment Technique (SWAT) - Leonardo, Leonardo; Sarvia, Elty (Universitas Sultan Ageng Tirtayasa, 2023)
Mental stress is a condition that can be caused by uncontrolled physical demands, environment, and social situations. In lecture activities, mental stress occurs in some students, reducing their performance at the lecture level. Mental stress in students tends to be high which can be caused by factors contained in lecture activities. Therefore, this study aims to analyze the mental workload experienced by students, especially Industrial Engineering students at X University class of 2020, and identify the factors that cause students' mental workload, and provide suggestions to help students overcome their mental workload. The method in this research is the Subjective Workload Assessment Technique (SWAT) to measure mental workload using respondent assessment and using Fishbone Diagram to find out the factors that cause high mental workload in students. The questionnaire was distributed to all students of class 2020 who were taking at least 18 credits in the odd semester of 2022-2023. The results of this method state that students of class 2020 have a mental burden on class activities and practicum activities. With a percentage of the time dimension of 46.78% in class activities and 55.34% in practicum activities followed by the effort dimension of 25.77% and 20.39%, the stress dimension of 27.45% and 24.27%. Based on the highest factors causing mental burden due to teaching and learning activities in class and practicum, it was found that the class of 2020 felt difficulties when studying quiz material, taking quizzes, studying practicum material, participating in practicum activities, working on practicum reports, and communicating with practicum partners. Some suggestions are to rearrange the lecture schedule or lecture hours, each lecturer makes an academic schedule for giving each assignment and quiz during the period of one semester, students are wiser in managing their free time, students take the number of credits according to their respective capacities, and so on.